A clinico-epidemiological profile of scrub typhus cases admitted in a tertiary hospital in South India - Purabi Phukan (Wolters Kluwer Medknow Publications, 2022)
Scrub typhus (ST) is a consistently underreported disease. The disease is spreading to newer areas, and an understanding of disease epidemiology is needed in the local Indian and current context. This study describes the demographic characteristics, monthly distribution, clinical and laboratory presentations, and treatment outcome of the ST cases recently identified. Case sheets of 15 ST patients diagnosed from January 2019 to December 2020 were analyzed. The majority of the patients were male. Eighty percent of the patients were from rural or suburban areas. Higher admission was observed from September to December. Fever (100%), skin rash (73.3%), body ache (53.3%), and vomiting (53.3%) were the most common clinical features. The onset of fever till the appearance of skin rash was 3 ± 1.2 days. The mean day from onset of symptoms till diagnosis was 6.8 ± 3.9 days. Eschar was found in only two patients. Nine (60%) patients already had complications at the time of admission. Most patients presented a laboratory picture of thrombocytopenia, neutrophilic leukocytosis, and anemia. Complications such as septic shock, acute kidney injury, and hepatic involvement were observed. All responded to doxycycline within 48 h. No fatalities were observed. Early clinical suspicion of ST among those with high fever, skin rash and thrombocytopenia, and transaminitis showed positive clinical outcome.